About the horizontal variability of effective radius in stratocumulus clouds. Issue 16 (23rd August 2016) - Magaritz‐Ronen, L.; Khain, A.; Pinsky, M.
Abstract: The role of turbulent mixing in formation of low horizontal variability of effective radius near the top of nondrizzling stratocumulus clouds is investigated in simulations of clouds observed during the Second Dynamics and Chemistry of Marine Stratocumulus field experiment. The clouds are simulated using a spectral bin microphysics Lagrangian‐Eulerian model consisting of ~2000 adjacent parcels moving in a turbulence‐like field with observed correlation properties. The parcels interact through drop sedimentation and turbulent mixing. It was found that the effective radius variability in the horizontal direction near cloud top does not exceed ~10% of the averaged value. Three different types of cloud parcels are revealed to be differently influenced by mixing: ascending slightly diluted parcels, cloudy parcels experiencing intense mixing with parcels from inversion, and initially dry parcels. The evolution of droplet size distributions in parcels belonging to these types is investigated. It is shown that in parcels of the first two types the values of effective radii do not change or change only slightly remaining close to the adiabatic value. In initially droplet‐free parcels effective radius rapidly reaches a value close to the adiabatic value, while liquid water content remains low. Therefore, turbulent mixing leads to establishing vertical profiles of effective radius, which are close to the adiabatic profile. Key Points: Turbulent mixing leads to reduction of horizontal variability of effective radius The effective radius is close to the adiabatic value at all heights The effects of mixing on the DSD varies in air volumes with different histories